Gene expression analyses in maize inbreds and hybrids with varying levels of heterosis - Stupar, Robert M (BioMed Central, 2008)
BACKGROUND: Heterosis is the superior performance of F(1 )hybrid progeny relative to the parental phenotypes. Maize exhibits heterosis for a wide range of traits, however the magnitude of heterosis is highly variable depending on the choice of parents and the trait(s) measured. We have used expression profiling to determine whether the level, or types, of non-additive gene expression vary in maize hybrids with different levels of genetic diversity or heterosis. RESULTS: We observed that the distributions of better parent heterosis among a series of 25 maize hybrids generally do not exhibit significant correlations between different traits. Expression profiling analyses for six of these hybrids, chosen to represent diversity in genotypes and heterosis responses, revealed a correlation between genetic diversity and transcriptional variation. The majority of differentially expressed genes in each of the six different hybrids exhibited additive expression patterns, and ~25% exhibited statistically significant non-additive expression profiles. Among the non-additive profiles, ~80% exhibited hybrid expression levels between the parental levels, ~20% exhibited hybrid expression levels at the parental levels and ~1% exhibited hybrid levels outside the parental range. CONCLUSION: We have found that maize inbred genetic diversity is correlated with transcriptional variation. However, sampling of seedling tissues indicated that the frequencies of additive and non-additive expression patterns are very similar across a range of hybrid lines. These findings suggest that heterosis is probably not a consequence of higher levels of additive or non-additive expression, but may be related to transcriptional variation between parents. The lack of correlation between better parent heterosis levels for different traits suggests that transcriptional diversity at specific sets of genes may influence heterosis for different traits.